Infestation of mistletoe Dendrophthoe pentandra (L.)Miq on various canopy shading and plants diversity in Purwodadi Botanic Garden: A study on medicinal plant Cassia fistula L. - Solikin Solikin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2020)
Mistletoe Dendrophthoe pentandra (L.)Miq is a parasitic plant commonly found parasitizing and infesting medicinal plants such as Cassia fistula L. This research aimed to investigate the infestation of D. pentandra on C. fistula on various trees canopy shading, infested host number and plant diversity. Study was conducted in Purwodadi Botanic Garden which located in Purwodadi, Pasuruan, East-Java during January-March 2020. Data Collection was conducted by explorative and descriptive methods in each block locations in the garden. Sampling plots were determined by purposive sampling method using 20x20 m per plot in each block where the tree of C. fistula found. The canopy shading was categorized as : open (4) = light interception > 90%, rather open (3) = light interception = 60-90%, rather shady (2) = light interception 30-60%, shady (1) (light interception < 30%). The result showed that the infestation of D. pentandra was affected significanly by the plant canopy shading and the infested host number in the blocks. The highest infestation of misletoe D. pentandra on C. fistula was found in the open canopy and the highest infested host plants in the block III.D with the parasite number 13 per plant. The tree plant diversity in the blocks tend to have negative correlation to the infestation of D. pentandra on C. fistula with r = -0.18.